A case-based narrative review on the structural myocardial changes associated with systolic dysfunction in severe aortic stenosis - Rajah, MeganR.; Doubell, Anton F.; Herbst, Philip G. (SA Heart Journal, 2024)
Severe aortic stenosis (AS) is not a disease of the valve only, but one involving the myocardium. Left ventricular systolic dysfunction in severe AS is associated with worse outcomes, despite aortic valve replacement (AVR). This case-based narrative review aims to highlight both the macro- and microscopic structural features of the myocardium in severe classic AS, with a particular focus on differentiating the afterload mismatch group from those with true contractile dysfunction. Left ventricular systolic dysfunction is associated with maladaptive patterns of left ventricular hypertrophy, mid-wall interstitial fibrosis, subendocardial replacement fibrosis secondary to ischaemia and possibly, low-grade chronic inflammation, and myocardial oedema. The underlying molecular signals appear to establish an ongoing cycle of maladaptive remodelling, but the initiating triggers remain poorly understood. Furthermore, features that differentiate those with afterload mismatch from those with true contractile dysfunction have been poorly investigated and further prospective research would provide important insight that could translate to earlier detection of those who may benefit from AVR before irreversible myocardial damage ensues, improved decision-making around management of these patients and the development of novel therapeutic strategies.